SEMIOTICS STUDY OF URBAN COMMUNITY DEPICTION AND LOCALITY ASPECTS IN POETRY MELIHAT API BEKERJA (2015) BY AAN MANSYUR - Anindya Diqza Syafiiqa (ELite Journal : International Journal of Education, Language, and Literature, 2022)
The image of an urban community is often reflected in several literary works as a form of expression of criticism of the situation in the urban community. The existence of the urban community has become one factor in the waning of the local Indonesian values. This research was done to depict the signs of local values and the portrayal of the urban society within the poem Melihat Api Bekerja (2015) by Aan Mansyur. This research was a literature review with the application of qualitative descriptive methods. The findings of this research were analyzed using Peirce’s semiotic theory through the trichotomy analysis of the figure of speech, imagery, and figurative language in the poem. It was found that the depiction of urban society was as busy with its world, while the locality aspect contained in it is a depiction through markers indicating that locality aspects have faded among urban communities. The depiction of the locality aspect is depicted through objects in the form of: 1) friendly attitude, 2) mutual cooperation, 3) traveling around the city by motorbike (using gasoline), and 4) friends are enemies. There was a significant relationship between the depiction of urban society and aspects of locality in poetry.